Survei Tingkat Pengetahuan, Pengalaman dan Sikap Civitas Akademik Universitas Faletehan terhadap Pencegahan dan Penanganan Kekerasan Seksual (Satgas PPKS) - Etty Nurkhayati; Suhroji Adha; Andiko Nugraha Kusuma; Fatoni Fatoni; Siti Nur Aliyah; Rifki Qamarrulloh; Dwi Rahmi (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
Sexual violence in higher education remains a serious issue that requires comprehensive prevention and effective institutional responses to ensure a safe and inclusive academic environment. As part of its commitment to implementing the mandate of the Indonesian Ministry of Education, Culture, Research, and Technology Regulation (Permendikbud) No. 30 of 2021, Faletehan University has established the Task Force for the Prevention and Handling of Sexual Violence (Satgas PPKS). This study aims to examine the level of knowledge, experience, and attitudes of lecturers and educational staff toward the Satgas PPKS. The study employed a descriptive survey method by distributing questionnaires through Google Forms. A total of 23 lecturers and educational staff participated in the survey. The collected data were analyzed descriptively to describe respondents’ understanding and perceptions of the role and function of the task force. The results indicate that the majority of respondents (86%) demonstrated a good level of knowledge and positive attitudes toward the Satgas PPKS, as reflected in high assessment scores ranging from 175 to 200 points. Nevertheless, a small proportion of respondents still obtained relatively low scores, indicating limited understanding of the task force’s duties and functions. These findings suggest that the Satgas PPKS has been widely recognized within the university community. However, continuous education, socialization, and capacity-building programs are still needed to strengthen awareness and ensure a more comprehensive understanding among all members of the academic community regarding the prevention and handling of sexual violence.